Digital sustainability and actor roles - Case Leading Company Ecosystem - Reitzer, Riikka (2024)
The purpose of this master’s thesis is to study leading company ecosystems funded by Business Finland. Sustainable development and digitalization require from the industries new solutions and wide-ranging cooperation in a continually changing business environment. The purpose of this thesis is to gain understanding of digitalization’s significance for sustainable development, the roles of different actors in these leading company ecosystems and factors impacting co-creation. The study was carried out as a qualitative case study. The research data was collected from the public roadmaps of leading companies and by semi-structured individual interviews of experts from the leading companies, Business Finland and ecosystem partners. The study results show that leading companies have several key areas where they rely on researching and developing innovative digital technologies to support also their sustainability objectives. The leading companies have a dominant role as they set the roadmaps and expected to steer these ecosystems toward achieving the ambitious missions which reflect their strategic goals. The relationships and dependencies make the ecosystem management and collaboration dynamic and complex. The findings suggest that the leading company ecosystems are a combination of knowledge, innovation, business and entrepreneurship ecosystems. The research findings indicate that by ensuring thorough project preparation, forming a well-rounded consortium, setting clear and realistic objectives, maintaining open communication, and planning exploitation, the collaborative projects can achieve their goals and drive significant industry development. The study underscores the importance of clearly defined roles, responsibilities and benefits for all ecosystem actors to prevent ambiguity and ensure effective collaboration.